Ljubljanski izumitelj Codelli (ob 50-letnici smrti) - Južnič, Stanislav (Vakuumist, 2003)
On 50th anniversary of Codelli's death his research on the early television was described. His work on electronic television for the American market was analysed. Other Codelli's inventions were mentioned.
Keywords: biografije; Codelli, Anton, 1875-1954; izumitelji; television; televizija